2014
DOI: 10.1002/2013jc009293
|View full text |Cite
|
Sign up to set email alerts
|

Focusing and vertical mode scattering of the first mode internal tide by mesoscale eddy interaction

Abstract: [1] Numerical experiments are performed using the MITgcm to investigate the interaction of a mode-one internal tide with barotropic and baroclinic mode-one mesoscale eddies. Results show that after a mode-one internal tide passes through a barotropic eddy, spatial hot and cold spots of energy flux are produced in beam-like patterns. The magnitude of the energy flux in the hot spots can exceed twice the incident flux while in the cold spots can reach nearly zero. Passing a mode-one internal tide through a mode-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 52 publications
(61 reference statements)
6
93
0
1
Order By: Relevance
“…The Amazon shelf break is particularly interesting because low-mode ITs generated at the shelf break and propagating into the open ocean may interact with eddies and the meandering field of steady currents such as the NBC and the NECC. Dunphy and Lamb (2014) showed that passing a mode-one IT through a mode-one baroclinic eddy results in IW scattering into higher modes -with implications for the…”
Section: J M Magalhaes Et Al: Internal Solitary Waves Off the Amazmentioning
confidence: 99%
“…The Amazon shelf break is particularly interesting because low-mode ITs generated at the shelf break and propagating into the open ocean may interact with eddies and the meandering field of steady currents such as the NBC and the NECC. Dunphy and Lamb (2014) showed that passing a mode-one IT through a mode-one baroclinic eddy results in IW scattering into higher modes -with implications for the…”
Section: J M Magalhaes Et Al: Internal Solitary Waves Off the Amazmentioning
confidence: 99%
“…Although internal tides with u/c ( 1 propagate as linear waves, they can be steered (Rainville and Pinkel 2006;Park and Watts 2006;Zaron and Egbert 2014;Kelly and Lermusiaux 2016) and scattered (Dunphy and Lamb 2014;Kelly and Lermusiaux 2016) by subtidal flows. Several studies have found that these phenomena appear to be dominated by linearized tide-mean flow interactions, even in fully nonlinear models (Zaron and Egbert 2014;Dunphy and Lamb 2014;Kelly and Lermusiaux 2016).…”
Section: Mean Flow Effectsmentioning
confidence: 99%
“…Several studies have found that these phenomena appear to be dominated by linearized tide-mean flow interactions, even in fully nonlinear models (Zaron and Egbert 2014;Dunphy and Lamb 2014;Kelly and Lermusiaux 2016).…”
Section: Mean Flow Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on linear wave theory, Cai et al (2008) studied internal waves in a shear background current, and found that in addition to the velocity shear across the pycnocline, the vertical structure of the horizontal velocity profile also had a significant influence on the evolution of internal waves. The interaction between mode-1 internal tides and mesoscale eddies was examined in Dunphy and Lamb (2014). The authors found that the interaction, essentially the bending of the paths followed by the wave energy, produced hot and cold spots of energy flux.…”
Section: Introductionmentioning
confidence: 99%